Task-based approach of language teaching - Carlos Orozco, Yessenia Esther (2020)
Today we live in a completely globalized world where knowing a foreign language, in this case English, has become a necessity because it acts as a vehicle of communication for people from different countries for labor, social and academic purposes. For this reason, this monograph entitled "Task-based approach of Language Teaching", proposes an innovative and different alternative to the traditional teaching methods that prevail in our classrooms, by proposing a new method embodied in practice through a didactic class session based on the task-based approach, so students learn through the development of meaningful activities that can be used in real-life; and thus, achieve the main objective, that students get to communicate in the foreign language.